PRACTICAL ASPECTS OF THE AGREEMENT BETWEEN THE POLISH REPUBLIC AND THE SLOVAK REPUBLIC FOR THE AVOIDANCE OF DOUBLE TAXATION WITH RESPECT TO TAXES ON INCOME AND PROPERTY - Jadwiga Szczotka (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2015)
The Slovak Republic is one of the most important economic partners of Poland. Crossborder cooperation between our two countries has been growing continuously for over twenty years. One of the areas of possible conflicts is the way of taxation regarding income and property. Until the end of 2014, Polish entrepreneurs could benefit from the optimization of certain tax burdens, including the non-taxation of dividends paid by companies established in Slovakia. The aim of the paper is to analyze tax problems faced by Polish entrepreneurs conducting business activity in Slovakia and to present the changes that come into force on 1 January 2015 with respect to taxation of income and property.